A new interval type-2 fuzzy approach for multi-scenario project cash flow assessment based on alternative queuing method and dependency structure matrix with a case study. (October 2020) - Mirnezami, Seyed Ali; Mousavi, Seyed Meysam; Mohagheghi, Vahid
Abstract: Managing project costs effectively, which comprises numerous aspects, is a highly complicated process for project managers that needs dependable cash knowledge in the entire life cycle of the project. Project managers' proficiency and anticipating dependable cash flows lead to substantial improvements in project costs management. Moreover, healthy cash flow prognostication for the whole construction project gives project managers a real insight into the identification of problems, and its deficiency results in the failure of firms even with big profits to maintain themselves as well. Therefore, predicting reliable cash flow and monitoring the progress of projects in terms of cash are essential to be considered. Furthermore, due to the existence of uncertainties in projects, it is necessary to find it as a significant part of different approaches. Building upon these, an innovative approach is presented in this paper to prognosticate project cash flow based on both type-2 fuzzy extension of dependency structure matrix for project scheduling with overlapping activities and extended alternative queuing method under type-2 fuzzy environment to adopt the best scenario. Moreover, type-2 fuzzy numbers are applied to address the uncertainty of activities. Subsequently, a real case study of a gas field development project is employed to represent the efficiency of proposed approach. Ultimately, a comparative study is conducted to validate the results, and superiorities of the proposed approach are addressed from different aspects. The results illustrate that the presented approach is capable of handling real project problems and providing project managers with a suitable tool to comprehend the cash conditions of the projects. Highlights: Developing a novel DSM method under TIT2FSs to address uncertainties. Proposing a new comprehensive approach to generate project cash flow. Taking a set of effective criteria, e.g., cost, quality, and safety criteria. Proposing a new satisfaction degree based an algorithm under TIT2FSs.